2003
DOI: 10.1590/s1517-83822003000400016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus on polyphosphate accumulation by Cunninghamella elegans

Abstract: The content of inorganic polyphosphate and the polymeric degree of these compounds were evaluated during the growth of Cunninghamella elegans in medium containing varying orthophosphate (Pi) concentrations. For this purpose, a combination of chemical methods for polyphosphate extraction and ultrastructural cytochemistry were used. The orthophosphate and glucose consumption was also determined during the fungal cultivation. At Pi concentrations of 0.5, 2.5 and 0.0 g/L, the maximum amounts of biomass were 3.18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Concerning oleaginous yeasts, phosphorus source limitation is beneficial for the lipid accumulation in nitrogen not-limited conditions (Huang et al 2018 ; Wang et al 2018 ; Wu et al 2010 ). In case of filamentous fungi, the effect of phosphorus was investigated in connection to polyphosphate accumulation (Lima et al 2003 ) or chitosan production (Safaei et al 2016 ). To the authors knowledge, there is no study reported the investigation of the role of phosphorus on the lipid accumulation in oleaginous filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning oleaginous yeasts, phosphorus source limitation is beneficial for the lipid accumulation in nitrogen not-limited conditions (Huang et al 2018 ; Wang et al 2018 ; Wu et al 2010 ). In case of filamentous fungi, the effect of phosphorus was investigated in connection to polyphosphate accumulation (Lima et al 2003 ) or chitosan production (Safaei et al 2016 ). To the authors knowledge, there is no study reported the investigation of the role of phosphorus on the lipid accumulation in oleaginous filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The exponential growth was observed for the first 3 days and the total biomass remained constant after 3 days. P is essential to the growth of cells because it is an indispensable element for cellular metabolisms, such as DNA, RNA and phospholipid biosynthesis and energy supply (de Lima et al ., ). Most fungal strains take P mainly in the growing phase and accumulate in cells as polyphosphate, the major fungal P reserve (Beever and Burns, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Lima et al [24] detected polyphosphate in the form of electron-dense granules in different cellular compartments of C. elegans , such as cell walls, vacuoles, cell membrane and cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Fungus species, Cunninghamella elegans , has great ability to accumulate phosphorus in the form of polyphosphate [24], to metabolize xenobiotic recalcitrant substances, such as polycyclic aromatic hydrocarbons-PAH [25], azo dyes used in the textile industry [26], oxidation of dibenzothiophene [27] and biotransformation of drugs [28], as well as it is able to grow in the presence of copper [29]. …”
Section: Introductionmentioning
confidence: 99%